Analyzing Students' Errors in Solving Sequence and Series Application Problems Using Newman Procedure - Nur Agustiani (International Journal on Emerging Mathematics Education, 2021)
This study aims to analyze the errors of students in solving the problem of applying sequence and series based on Newman's rules. This research uses descriptive analysis method. The subjects of this study were first semester students majoring in business administration at Muhammadiyah University of Sukabumi. The data collection used test and interview methods. Based on the results of data analysis using the Newman error analysis procedure, it is concluded that students made 8.9% reading errors, 18.9% comprehension errors, 32.2% transformation errors, 42.2% process skills errors, and 43.3% encoding errors. The percentage of reading errors up to encoding errors has increased because students cannot solve the problem correctly after encountering obstacles at the beginning. Error analysis can be used as reference material for lecturers in designing learning that can overcome student errors in working on the applied of sequence and series.